Phenolic content of Terminalia catappa L. leaf and toxicity evaluation on red hybrid tilapia (Oreochromis sp.). Issue 2 (1st December 2022) - Yakubu, Yahaya; Ahmad, Muhammad T.; Chong, Chou M.; Ismail, Intan S.; Shaari, Khozirah
Abstract: Despite the use of Terminalia catappa (TC) leaf by traditional fish farmers around the world to improve the health status of cultured fish, there is a paucity of information on comprehensive metabolite profile and the maximum safe dose of the plant. This study aims at profiling the methanol leaf extract of T. catappa, quantifying total phenolic content (TPC) as well as the total flavonoid content (TFC) and evaluating its acute toxicity on blood, plasma biochemical parameters and histopathology of some vital organs in red hybrid tilapia ( Oreochromis sp.). The experimental fish were acclimatised for 2 weeks and divided into six groups. Group (1) served as a control group and was administered 0.2 ml, g −1 of phosphate buffer saline (PBS). Groups 2–6 were orally administered T. catappa leaf extracts (0.2 ml.50 g −1 ) in the following sequence; 31.25, 62.5, 125, 250 and 500 mg.kg −1 body weight. The metabolites identified in T. catappa using liquid chromatography‐tandem mass electrospray ionisation spectrometry (LC‐ESI‐MS/MS) revealed the presence of organic acids, hydrolysable tannins, phenolic acids and flavonoids. Phenolic quantification revealed reasonable quantity of phenolic compounds (217.48 μg GAEmg −1 for TPC and 91.90 μg. QCEmg −1 for TFC). Furthermore, there was no significant difference in all the tested doses in terms of blood parameters and plasma biochemical analysis except for the packed cell volume (PCV) at 500 mg.kg −1 when compared to the control. Significant histopathological changes were observed in groups administered with the extract at 125, 250 and 500 mg.kg −1 doses. To a very large extent it is therefore safe to administer the extract at 31.25 and 62.5 mg.kg −1 in tilapia.